Active testing and edge analysis for road centreline extraction - Dal Poz, A. P. [UNESP]; Silva, M. A.O. [UNESP] (My University, 2002)
As in the foreseeable future a human will be expected to remain as part of the object extraction system, semi-automated road extraction methods are still important. Following this trend, this paper presents a semi-automated method for extracting road segments from medium- and high-resolution images based on active testing and edge analysis. The method is based on two sequential and independent stages. Firstly, an active testing method is used to extract an approximated road centreline, which is based on a sequential and local exploitation of the image. Secondly, an iterative strategy based on edge analysis and the approximated centreline is used to measure precisely the road centreline. Based on results obtained using a medium-resolution test image, the method seems to be very promising. In general, the method prove to be very accurate whenever the roads are characterised by two well-defined anti-parallel edges and robust even in the presence of larger obstacles, as e.g. trees and shadows.
Keywords: Edge analysis; Matching; Road extraction; Semi-automation; Vision